2011
DOI: 10.3109/14992027.2010.540722
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of hearing loss in a ‘normally-hearing’ college-student population

Abstract: We report pure-tone hearing threshold findings in 56 college students. All subjects reported normal hearing during telephone interviews, yet not all subjects had normal sensitivity as defined by well-accepted criteria. At one or more test frequencies (0.25–8 kHz), 7% of ears had thresholds ≥25 dB HL and 12% had thresholds ≥20 dB HL. The proportion of ears with abnormal findings decreased when three-frequency pure-tone-averages were used. Low-frequency PTA hearing loss was detected in 2.7% of ears and high-freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 62 publications
2
44
0
3
Order By: Relevance
“…Use of personal music players has already been correlated with EHF deficits (Peng et al, 2007; Figueiredo et al, 2012); our own analysis of the relationship between thresholds at conventional test frequencies, ranging from 250 Hz to 8 kHz, is consistent with this literature in that deficits as a function of music player were observed only at the highest conventional test frequencies (6 and 8 kHz) (Le Prell et al, 2011). One of the main shortcomings of the existing literature that seeks to identify relationships between music player use and hearing deficits is the limited information on other sources of noise to which study participants are routinely exposed.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Use of personal music players has already been correlated with EHF deficits (Peng et al, 2007; Figueiredo et al, 2012); our own analysis of the relationship between thresholds at conventional test frequencies, ranging from 250 Hz to 8 kHz, is consistent with this literature in that deficits as a function of music player were observed only at the highest conventional test frequencies (6 and 8 kHz) (Le Prell et al, 2011). One of the main shortcomings of the existing literature that seeks to identify relationships between music player use and hearing deficits is the limited information on other sources of noise to which study participants are routinely exposed.…”
supporting
confidence: 84%
“…In addition, inclusion criteria required that thresholds for the right and left ears be no more than 15 dB HL apart. Finally, if air conduction thresholds were 15 dB HL or higher (worse), bone conduction testing was administered and the difference between air and bone thresholds was required to be 10 dB or less (see Le Prell et al, 2011; Le Prell et al, 2012). All of the participants described in this report met the aforementioned inclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Vogel et al (2010) reports that males are more likely to select higher PLLs than females, which is supported by McNeill et al (2010) reporting male PLLs to be a median of 7dBA higher than those of females. Le Prell et al (2011) also found that males using PLDs had significantly elevated hearing thresholds compared to females. Therefore, it is of vital importance that this group of individuals are made aware of immediate and future dangers, and provided with essential influence and education that will motivate and encourage a change in their listening habits.…”
Section: Discussionmentioning
confidence: 84%
“…Additionally, the other possible influential factor appears to be gender differences for both PLLs and durations of use (Le Prell et al, 2011, Vogel et al, 2010, McNeill et al, 2010. For example, Vogel et al (2010) reports that males are more likely to select higher PLLs than females, which is supported by McNeill et al (2010) reporting male PLLs to be a median of 7dBA higher than those of females.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation